2021
DOI: 10.1155/2021/5122380
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine Leptochloa chinensis Inhibits the Malignant Behaviors of Renal Cell Carcinoma 786-O Cells by Regulating the mTOR Pathway

Abstract: Background. Renal cell carcinoma (RCC) is a common malignant tumor of the urinary system that seriously threatens human life and health. This study aims to explore the role of the traditional Chinese medicine Leptochloa chinensis in the pathogenesis of RCC. Meanwhile, this study also revealed the molecular biological mechanism of its antitumor activity. Methods. Human RCC 786-O cells were cultured in the RPMI-1640 medium, which contains different concentrations of Leptochloa chinensis (1,000, 3,000, and 9,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Modern researches have shown [20] that Chinese medicine-assisted RCC postoperative treatment has a relatively clear role in improving patients' clinical symptoms, protecting renal function, regulating body immunity, preventing tumor recurrence and metastasis, and improving the quality of life of patients. Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment. Zhong et al [22] found that combined Chinese medicine therapy was more stable for patients with renal cancer after laparoscopic radical resection and prolonged survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Modern researches have shown [20] that Chinese medicine-assisted RCC postoperative treatment has a relatively clear role in improving patients' clinical symptoms, protecting renal function, regulating body immunity, preventing tumor recurrence and metastasis, and improving the quality of life of patients. Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment. Zhong et al [22] found that combined Chinese medicine therapy was more stable for patients with renal cancer after laparoscopic radical resection and prolonged survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the holistic view and syndrome differentiation, traditional Chinese medicine believes that renal cell cancer is caused by deficiency of kidney qi and aggregation of pathogenic toxins [ 4 ]. The application of TCM treatment can improve the healthy qi, stabilize the cancer focus, prevent recurrence and metastasis, and thus achieve the purpose of improving the quality of life of patients and prolonging their survival [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…e application of TCM treatment can improve the healthy qi, stabilize the cancer focus, prevent recurrence and metastasis, and thus achieve the purpose of improving the quality of life of patients and prolonging their survival [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…TCM combined with chemotherapeutic drugs can act on multiple pathways at the same time, enhance the anti-tumor efficacy of chemotherapeutic drugs, reduce the adverse reactions of chemotherapeutic drugs and also avoid the emergence of drug resistance [ 8 ]. So the TCM combined with targeted drugs, such as sorafenib, has a broad application prospect in the treatment of cancer [ 12 ]. Resveratrol is a natural polyphenolic antioxidant, which is widely present in grapes, peanuts and a variety of TCMs [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%